IgG1 antibodies to acetylcholine receptors in 'seronegative' myasthenia gravis. - Leite, M; Jacob, S; Viegas, S; Cossins, J; Clover, L; Morgan, B; Beeson, D; Willcox, N; Vincent, A (2008)
Only around 80% of patients with generalized myasthenia gravis (MG) have serum antibodies to acetylcholine receptor [AChR; acetylcholine receptor antibody positive myasthenia gravis (AChR-MG)] by the radioimmunoprecipitation assay used worldwide. Antibodies to muscle specific kinase [MuSK; MuSK antibody positive myasthenia gravis (MuSK-MG)] make up a variable proportion of the remaining 20%. The patients with neither AChR nor MuSK antibodies are often called seronegative (seronegative MG, SNMG). There is accumulating evidence that SNMG patients are similar to AChR-MG in clinical features and thymic pathology. We hypothesized that SNMG patients have low-affinity antibodies to AChR that cannot be detected in solution phase assays, but would be detected by binding to the AChRs on the cell membrane, particularly if they were clustered at the high density that is found at the neuromuscular junction. We expressed recombinant AChR subunits with the clustering protein, rapsyn, in human embryonic kidney cells and tested for binding of antibodies by immunofluorescence. To identify AChRs, we tagged either AChR or rapsyn with enhanced green fluorescence protein, and visualized human antibodies with Alexa Fluor-labelled secondary or tertiary antibodies, or by fluorescence-activated cell sorter (FACS). We correlated the results with the thymic pathology where available. We detected AChR antibodies to rapsyn-clustered AChR in 66% (25/38) of sera previously negative for binding to AChR in solution and confirmed the results with FACS. The antibodies were mainly IgG1 subclass and showed ability to activate complement. In addition, there was a correlation between serum binding to clustered AChR and complement deposition on myoid cells in patients' thymus tissue. A similar approach was used to demonstrate that MuSK antibodies, although mainly IgG4, were partially IgG1 subclass and capable of activating complement when bound to MuSK on the cell surface. These observations throw new light on different forms of MG paving the way for improved diagnosis and management, and the approaches used have applicability to other antibody-mediated conditions.